Fundraising with Businessess - Waters, Joe (John Willey & Son, 2014)
This book will give you the hands - on advice and practical tactics you need to raise money with businesses. More over, reader will have a digital lifeline to additional learning and help, ensuring the book will always be current and up-to-date.